IMPLEMENTASI GAME BASED LEARNING (GBL) PADA KARAKTER KREATIF SISWA KELAS 3 SDN KEDAUNG 1 - Fitria Rosmi; Anisa Putri Salwa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine how the application of the Game Based Learning (GBL) learning model to the creative character of 3rd grade students of SDN Kedaung 1. The problems found in the class are that students are still less brave to express ideas, are not active in learning, and are not used to thingking creatively. This study uses a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation. The subjects of this study were 3rd grade teachers and 30 students off class 3C. the results of the study show that the use of game based learning models, especially the Mystery Of Puzzle game, can create a fun learning atmosphere and make students more enthusiastic and brave to express ideas. Students also appear more active and work together in groups. With the Game Based Learning (GBL) learning model, students become more creative in thinking and solving problems in learning. From these results it can be concluded that Game Based Learning (GBL) can be one of the right ways to improve the creative character of 3rd grade students of SDN Kedaung 1.